Object-relational Features for Modeling and Analysis of Spatio-temporal Data - Kamruzzaman, A. Z. M; Wahid, Mohd. Taib (2006)
The age of discovery, description, and classification of biodiversity is entering a new phase. In responding to the importance and uses of the large number of biodiversity data of Malaysia make it essential for their biodiversity to be conserved. In order to manage large number of biodiversity data, it is essential to develop a data model which is a new integrated and support spatio-temporal data. Recently, we propose a conceptual spatio-temporal objectrelational biodiversity data model and which is being tested with Malaysian biodiversity data and has been loaded to oracle database. The main objectives of this paper are new aspects of using object-relational feature of the underlying database management system Oracle to improve the extensibility and flexibility of data models, enhance interoperability and analyzing potential as well as to ensure consistency by defining standards based on abstract data types. The object-relational extension of data models can be combined with data pyramid framework techniques to analyze present, past and future data. In addition to this, by using this model forest department, researchers, as well as natural recourses will be helpful.